Pengaruh Kondisi Gelap Terang Terhadap Biodegradasi Styrofoam Menggunakan Larva Tenebrio Molitor - Jessar Hendrianto; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Styrofoam or polystyrene (PS) can make block water channel, greenhouse effect and make a big contribution in global warming, interfering with a various equilibrium environmental and health components. One of styrofoam waste treatment is a biodegradation by utilizing mealworm (Tenebrio molitor larva). This research aims to calculate the value of degradation (%biodegradation) efficiency with additional nutrients and %Survival Rate of larva. In this study variations we make comparation in dark and light conditions, The result highest of %biodegradation Styrofoam is a Styrofoam dark condition with 57% value and lowest value is a Styrofoam in light condition with 51%. While for the highest %SR dark condition is 65% and light condition with 75%.Key Word : Styrofoam, Survival Rate, Biodegradation, Tenebrio molitor Larva.